2017
DOI: 10.1186/s12936-017-1836-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of home-based management on malaria outcome in under-fives presenting in a tertiary health institution in Nigeria

Abstract: BackgroundHome-based management of malaria involves prompt delivery of effective malaria treatment at the community by untrained caregiver. The aim of this study was to document home-based treatment of suspected malaria by non-medical caregivers and to identify its health impact on malaria outcome (severe malaria prevalence, parasite load and mortality) in children (6–59 months).MethodsA descriptive cross-sectional study carried out from June 2012–July 2013. Data was obtained by researcher-administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…[14][15][16] Due to this, the choice for alternative care outside health facilities is high among the lower social class hence the high patronage of the PMVs as the first line healthcare provider as observed in this study. 8,13 The fact that level of education was not significantly associated with HSB suggests that economic power could be a major factor in the decision to visit PMVs as the first health care provider than to go to the health centres/ hospitals which in most cases cost more.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[14][15][16] Due to this, the choice for alternative care outside health facilities is high among the lower social class hence the high patronage of the PMVs as the first line healthcare provider as observed in this study. 8,13 The fact that level of education was not significantly associated with HSB suggests that economic power could be a major factor in the decision to visit PMVs as the first health care provider than to go to the health centres/ hospitals which in most cases cost more.…”
Section: Discussionmentioning
confidence: 99%
“…8,13 Although the close-to-client phenomenon of the PMVs could be a major factor warranting the first point of visit during illnesses at the community level; however, some poor practices of these PMVs contribute significantly to poor disease outcome. [8][9][10][11][12]13 Figure 1 Symptoms of severe malaria as volunteered by the caregivers There were multiple responses and features at presentation* Figure 2 Features of severe malaria identified by the physician There were multiple responses and features at presentation* For example, studies have shown that the prescription pattern of antimalarial drugs, especially for paediatric age groups by the PMVs is poor and most times inaccurate. 24 Etiaba et al 12 recently documented that the first line visit of most caregivers to the PMVs contributed significantly to wrong diagnosis, inability to detect malaria co-morbidities, worsening of malaria morbidities; and perhaps increased mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations